Prognostic factors for work disability in patients with chronic widespread pain and fibromyalgia: protocol for a cohort study - Robin Christensen; Marius Henriksen; Eva Ejlersen Wæhrens; Henning Bliddal; Lars Erik Kristensen; Karsten Thielen; Henning Locht; Kirstine Amris; Pernille H Duhn (BMJ Open)
Introduction The association between chronic widespread pain (CWP) and disability is well established. Although research support large interindividual differences in functional outcomes, limited studies are available on the socio-economic consequences of offering stratified treatment based on prognostic factors. Identification of predictors of long-term functional outcomes such as work disability as a critical consequence, could assist early and targeted personalised interventions. The primary objective of this cohort study is to identify prognostic factors for the primary endpoint work status (employed and working vs not working) in patients with CWP assessed 3 years from baseline, that is, at referral for specialist care.Methods and analyses Data are collected at the diagnostic unit at Department of Rheumatology, Frederiksberg Hospital. The first 1000 patients ≥18 years of age registered in a clinical research database (DANFIB registry) with CWP either ‘employed and working’ or ‘not working’ will be enrolled. Participants must meet the American College of Rheumatology 1990 definition of CWP, that is, pain in all four body quadrants and axially for more than 3 months and are additionally screened for fulfilment of criteria for fibromyalgia. Clinical data and patient-reported outcomes are collected at referral (baseline) through clinical assessment and electronic questionnaires. Data on the primary endpoint work status at baseline and 3 years from baseline will be extracted from the Integrated Labour Market Database, Statistics Denmark and the nationwide Danish DREAM database. Prognostic factor analysis will be based on multivariable logistic regression modelling with the dichotomous work status as dependent variable.Ethics and dissemination Sensitive personal data will be anonymised according to regulations by the Danish Data Protection Agency, and informed consent are obtained from all participants. Understanding and improving the prognosis of a health condition like CWP should be a priority in clinical research and practice. Results will be published in international peer-reviewed journals.Trial registration number NCT04862520.